PRAGMATIC INTERPRETATION OF PAREMIAS - D. S Turdalieva (Journal Park Publishing, 2022)
In this article, the issues of pragmatic interpretation of paremia are presented in an approach to the views of linguists.The use of proverbs and parables by the speaker in his speech for various purposes is also illustrated on the basis of examples. The places of formation of linguistic pragmatics are also covered.
Keywords: paremia; subject of speech; pragmatic information